Study of the scientific production of the publications in Mexico refered to the cataloguing of documents: 1990-2009 - Clausó García, Adelina; Carpallo Bautista, Antonio (Revista General de Información y Documentación, 2012)
This article evaluates Mexican scientific monograph production, magazine articles, congresses and its communications, as well as Thesis, Dissertations and Academic Reports about Cataloguing of documents between 1990 and 2009, from the registers found in INFOBILA database, in CLASE database, in the OPAC of National Library of Mexico, in the OPAC of CUIB library and in Investigación Bibliotecológica magazine. The publication date, authorship, genre, publishing places and entities are studied, among others interest aspects that make possible an approach to this area of the knowledge.